Factors Explaining Management Preferences of Accounting for Goodwill Prior to the Implementation of IFRS 3: A Cross-Country Study - Astami, Emita W. (Gadjah Mada International Journal of Business, 2006)
This study provides evidence on the cross sectional relationship between firm economic variables and management preferences in the selection of an accounting technique for goodwill. It examines goodwill accounting policy disclosures in the 2000/2001 annual reports of 269 listed companies in the five countries: Australia, Hong Kong, Indonesia, Malaysia, and Singapore. The key focus is managementâs choice of accounting techniques for the treatment of goodwill.The results show that accounting practices for goodwill vary significantly across country of origins and across industry groups. Two economic variables significantly explain management preferences of accounting for goodwill. The finding shows that the higher a companyâs financial leverage ratio the company managers prefer to write off goodwill immediately against income or to capitalize and amortize it in a sorter period of time. The higher a companyâs size, the more likely the company would write-off of goodwill to balance sheet reserves. Thus, this study provides empirical evidence that management preferences of accounting for goodwill have economic consequences.